Adolescent type D personality and social networking sites addiction: A moderated mediation model of restorative outcomes and affective relationships. (January 2019) - Nie, Jia; Li, Wendi; Wang, Pengcheng; Wang, Xingchao; Wang, Yuhui; Lei, Li
Highlights: Type D personality was positively related to social networking sites addiction. Restorative outcomes mediated the link between Type D personality and social networking sites addiction. Affective relationships with friends moderated the mediation effect. Abstract: Type D personality denotes the joint tendency towards negative affectivity and social inhibition. The recent research has regarded Type D personality as a risk factor of social networking sites addiction. The current study aimed to test whether restorative outcomes would mediate the relation between Type D personality and social networking sites addiction, and whether affective relationships would moderate simultaneously the mediating process. A valid sample of 679 adolescents (mean age = 13.29 ± 0.77 years) participated in our paper-and-pencil survey. Results showed that, after controlling for age and gender, Type D personality positively correlated with social networking sites addiction, and it increased social networking sites addiction via escalating participants' restorative outcomes. Moreover, only affective relationships with friends moderated the mediating effect: for adolescents with low levels of affective relationships with friends, the indirect effect of Type D personality on social networking sites addiction was significant; contrarily, the indirect effect for high levels of affective relationships with friends was non-significant. The current study indicated that Type D personality as a risk factor interacted with other factors (e.g., affective relationships with friends) to contribute to adolescent social networking sites addiction. The limitations and practical implications were discussed.